2018
DOI: 10.3389/fmicb.2018.01012
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Salix Genotypes Promotes Root Colonization With Dark Septate Endophytes and Changes P Cycling in the Mycorrhizosphere

Abstract: The roots of Salix spp. can be colonized by two types of mycorrhizal fungi (ectomycorrhizal and arbuscular) and furthermore by dark-septate endophytes. The fungal root colonization is affected by the plant genotype, soil properties and their interactions. However, the impact of host diversity accomplished by mixing different Salix genotypes within the site on root-associated fungi and P-mobilization in the field is not known. It can be hypothesized that mixing of genotypes with strong eco-physiological differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
5
13
0
Order By: Relevance
“…A general effect of the species and the growth design on the phosphatase activity under Salix is in agreement with the results of the mycorrhizosphere observation by Baum et al [47]. However, only two Salix species were investigated in the present study due to the limitation of available plant variants at the test site Rostock in Germany (only Loden and Tora were present).…”
Section: Discussionsupporting
confidence: 91%
“…A general effect of the species and the growth design on the phosphatase activity under Salix is in agreement with the results of the mycorrhizosphere observation by Baum et al [47]. However, only two Salix species were investigated in the present study due to the limitation of available plant variants at the test site Rostock in Germany (only Loden and Tora were present).…”
Section: Discussionsupporting
confidence: 91%
“…A low ECM and endophyte diversity in roots in all genotype treatments in the Rostock trial were also shown previously (Baum et al, 2018), but the mycorrhizal root tips did not show a strong increase in ECM colonization in the 2-mixture compared to monocultures as the increase in the proportion ECM fungi in soil in the Rostock 2-mixture in the present study. In Uppsala, site conditions were more heterogeneous (block effects).…”
Section: Few Effects Of Plant Genotype Diversity On Soil Fungal Diversitysupporting
confidence: 87%
“…As a bridge linking the plant and soil environment (Peterson et al, 2008), DSE fungi increases the interaction between plants and soil and expands the pool of N and P that can be used by host plants because they secrete lots of enzymes to mineralize organic N and insoluble P in soil into available forms; thus, promoting the growth and tolerance of plants to stressful conditions (Newsham, 2011; Monica et al, 2015). Although the degradation of specific organic nutrient sources can differ among different DSE species (Della Monica et al, 2015), studies have suggested that DSE fungi can mineralize organic compounds that contain N and P, improving their availability to plants (Baum et al, 2018). A recent study using Asparagus demonstrated that Phialocephala fortinii isolates can convert soil organic nutrients to available forms to support the plant growth.…”
Section: Discussionmentioning
confidence: 99%